An additive for reducing the number of pinholes in copper foil and a method of using the additive
By using additives containing copper acid strong displacement agent, sodium polydisulfide dipropane sulfonate and gelatin in the ultra-thin electrolytic copper foil, the light transmittance points and pinhole problems in the ultra-thin copper foil are solved, and the copper foil is realized Improve physical performance and productivity.
Patent Information
- Application Number
- CN202210921483.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing ultra-thin electrolytic copper foil production process, there are still many light-transmitting points or pinholes, resulting in the physical performance of copper foil being unqualified. Some larger pinholes may even penetrate slurry, which increases production costs. and tossing time.
In the production process of ultra-thin electrolytic copper foil, an additive including water, copper acid strong displacement agent, sodium polydisulfide dipropane sulfonate and gelatin is used to change the electrolysis process by adjusting the concentration and addition flow rate of the additives. The electric layer structure and the effective area of the electrode make the current density evenly distributed, reducing the light-transmitting holes and pinholes on the copper foil surface.
By using this additive and process, the number of light-transmitting points and pinholes on the ultra-thin copper foil can be greatly reduced, and reduced to less than 5/m2, avoiding the occurrence of slurry penetration, improving the physical properties and quality of the copper foil, and reducing the Drag waste time to improve yield and production efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil production technology, and in particular to an additive for reducing the number of copper foil pinholes and a use method thereof. Background Art
[0002] Industrial copper foil is usually divided into two categories: rolled copper foil and electrolytic copper foil. Rolled copper foil has good ductility, while electrolytic copper foil has the advantage of low manufacturing cost and is suitable for large-scale production. Electrolytic copper foil refers to metal copper foil produced by electrolysis using copper as the main raw material.
[0003] With the development of the electronic information industry, the requirements for lightweight and integrated electronic products are becoming increasingly higher. As a basic material in the electronics industry, electrolytic copper foil not only puts forward higher requirements on the physical and chemical performance indicators of the product such as tensile strength, elongation, peel strength, and oxidation resistance, but also requires the copper foil's micro-grain structure and surface micro-morphology to be more uniform and fine.
[0004] In the lithium battery industry or the electronics industry, the thickness of the electrolytic copper foil currently used is getting lower and lower, and the thickness of ultra-thin electrolytic copper foil is reduced to 10 microns, 6 microns or even 4 microns. However, the thinner the copper foil, the easier it is to cause defects in copper foil production. For ultra-thin copper foil, everything from raw materials to rolling rollers to rolling oil, and even larger dust in the air can cause defects such as pinholes and light spots.
[0005] Based on the above factors, the industry generally believes that pinholes are mainly related to gas content, inclusions, compounds and component segregation. Effective copper liquid purification, filtration and grain refinement can help reduce pinholes.
[0006] At present, the Chinese patent with publication number: CN1958863A discloses an ultra-thin double-sided high-performance electrolytic copper foil and its preparation method, which adopts a new electrolytic process and a new organic mixed additive. The organic mixed additive is prepared with polyethylene glycol, sodium polydisulfide dipropane sulfonate, thiourea and sodium methylthiocarbamoyl propane sulfonate.
[0007] This method is simple and practical, and its production cost is much lower than that of rolled copper foil, which can greatly reduce the production cost of printed circuit boards and polymer lithium-ion batteries. The thickness of the copper foil can be no more than 8μm, the tensile strength is greater than 40kg / square millimeter, and the elongation is greater than 5%. However, the ultra-thin copper foil produced by this process still has many light-transmitting points or pinholes, resulting in unqualified physical properties of the copper foil. Some larger pinholes may even cause the slurry to penetrate. In addition, it takes a lot of time to drag the waste copper foil, which increases the production cost. Summary of the invention
[0008] The present invention aims at the above technical problems, overcomes the disadvantages of the prior art, and provides an additive for reducing the number of pinholes in copper foil.
[0009] Technical effect: When producing ultra-thin electrolytic copper foil, adding the fatty alcohol additive of the present invention can greatly reduce the number of light-transmitting spots and pinholes on the ultra-thin copper foil. The number of light-transmitting holes and pinholes on the copper foil produced by using the additive and process can be reduced to 5 / m 2 Within, the occurrence of slurry penetration is avoided, the physical properties of copper foil are improved, the quality of copper foil is improved, and the time required for dragging waste copper foil is reduced, which greatly improves the yield and production efficiency of copper foil.
[0010] The technical solution further defined in the present invention is: a method for using an additive for reducing the number of pinholes in copper foil, wherein the production of copper foil includes copper dissolving, raw foil preparation and surface treatment steps, and the additive is added to a copper sulfate solution together with an electrolyte after the copper dissolving step, and the method for using the additive includes the following steps:
[0011] S1: Additive concentration configuration, add 5-8L of pure water to every 1g of additive to form an additive solution, and the addition flow rate of the additive solution is 5-20L / h;
[0012] S2: Production debugging, the additive is added before the solution inlet flowmeter, the initial addition flow of the additive solution is controlled at 5L / h, after the additive is configured, several raw foils are started for online polishing, the polishing parameters are speed 250 / swing 230, during the polishing process, it is necessary to pay attention to whether there is a color difference change on the copper foil surface, if there is an obvious color difference change, stop the machine immediately for adjustment;
[0013] S3: Visual inspection: after polishing is completed, the speed is increased to 6 microns, and a copper foil sample with a size of 50cm*1380mm is cut and visually inspected on a light box to determine the number of light-transmitting points or pinholes on the copper foil sample and compare it with the preset number. If the number of light-transmitting points or pinholes is greater than the preset number, the flow rate of the additive solution is increased, and the production debugging and visual inspection steps are repeated;
[0014] S4: Stable production, after production debugging and visual inspection, determine the addition flow rate of qualified additive solution and enter the stable copper foil production process;
[0015] In step S4, the concentration of the additive solution needs to be inspected and the flow rate calibrated every 2 hours.
[0016] Furthermore, in step S1, 6 to 6.5 L of pure water are added to every 1 g of additive to prepare the additive solution, and the optimal amount is to add 220 L of pure water to every 35 g of additive.
[0017] In the aforementioned method for using an additive for reducing the number of pinholes in copper foil, in the production debugging step, the addition flow rate of the additive solution is increased by 5 L / h each time, and the optimal range of the addition flow rate of the additive solution is 10 to 15 L / h.
[0018] The present invention also provides an additive for reducing the number of pinholes in copper foil, comprising water and substances with the following concentrations:
[0019] Acid copper strong moving agent 0.08~0.2g / L
[0020] Sodium polydisulfide propane sulfonate (SPS) 0.02~0.05g / L
[0021] Gelatin 0.01~0.04kg / L.
[0022] The aforementioned additive for reducing the number of pinholes in copper foil, the acid copper strong moving agent is fatty amine ethoxy sulfonate (AESS), and the optimal content of AESS is 0.16 g / L.
[0023] The optimal content of SPS in the aforementioned additive for reducing the number of pinholes in copper foil is 0.04 g / L.
[0024] The aforementioned additive for reducing the number of pinholes in copper foil has an optimal gelatin content of 0.02 kg / L. Gelatin is bone glue and collagen, with a ratio of bone glue to collagen of 7:3 and a molecular weight of 18,000 to 25,000 Da.
[0025] The beneficial effects of the present invention are:
[0026] (1) In the present invention, in the production process of electrolytic copper foil, the factors that affect the number of light-transmitting holes and pinholes in the copper foil include, in addition to the influence of the quality of the raw materials themselves and the production environment, the uniformity of copper electrodeposition and current density distribution in the solution during the reaction process will also affect the thickness and quality of the copper foil at various positions. The thinner the copper foil, the greater the impact. After adding the additive, the double electric layer structure and the effective area of the electrode at various positions during the electrolysis process can be changed, so that the current density distribution at various positions is uniform, the interface tension on the electrode surface is reduced, the wettability of the electrolyte and cathode interface is increased, and the preferential growth during the copper deposition process is reduced, thereby achieving the purpose of eliminating pinholes and refining grains. Not only does it reduce the number of light-transmitting holes and pinholes on the copper foil surface, but it also improves the copper stacking uniformity and the flatness of the copper foil surface, thereby improving the various physical properties of the copper foil.
[0027] (2) In the present invention, the number of light-transmitting points and pinholes on the surface of copper foil per square meter produced by the additive and the adding method can be reduced to less than 5, and the size of the light-transmitting points and pinholes can also be greatly reduced, thereby avoiding the occurrence of slurry penetration and meeting the use requirements of customers; when the copper foil production is started, it takes a period of time to remove the waste copper foil, that is, to remove the copper foil produced when the material does not reach the optimal production conditions at the beginning and has many light-transmitting points and pinholes. The copper foil produced by the additive and the adding method can greatly reduce the time required for removing the waste copper foil, reducing the time of removing the waste copper foil from at least 4 hours to 1 hour, thereby greatly improving the production efficiency of the copper foil;
[0028] (3) In the present invention, the copper foil produced by using the additive and the adding method has high quality, high production efficiency, greatly improved yield rate, no significant waste of copper foil, and after reducing the light transmission points and pinholes on the surface of the copper foil, the physical properties of the copper foil are greatly improved, and it is not easy to cause hard wrinkles and tearing edges; the copper foil production process can be carried out continuously, thereby improving the utilization rate of the equipment;
[0029] (4) In the present invention, the time for dragging the waste copper foil due to abnormal light transmission points / pinholes after the cathode roller is polished is effectively reduced, and the time for dragging the waste copper foil is reduced from the original 4 hours to 1 hour, which effectively improves the production efficiency and the yield rate, and the weight of the waste copper foil is controlled within a reasonable range, thereby reducing the amount of scrapped copper foil; at the same time, the number of light transmission points and pinholes after the cathode roller is polished is effectively reduced, from dense light transmission points (pinholes) to less than 5 light transmission points (pinholes) per square meter, thereby meeting customer requirements and reducing customer complaints; the physical properties of the ultra-thin copper foil after polishing meet the production requirements, effectively reducing the occurrence of abnormalities such as wrinkling and tearing during the production process, ensuring that the production process is uninterrupted and improving the utilization rate of production machines. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, a detailed description is given below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] The present embodiment provides an additive for reducing the number of pinholes in copper foil, including water, to which substances of the following concentrations are added:
[0033] Acid copper strong moving agent 0.08~0.2g / L
[0034] Sodium polydisulfide propane sulfonate (SPS) 0.02~0.05g / L
[0035] Gelatin 0.01~0.04kg / L.
[0036] Among them, the acid copper strong moving agent is fatty amine ethoxy sulfonate (AESS), and the gelatin is bone glue and collagen.
[0037] In the production of electrolytic copper foil, additives are usually added to the electrolyte to regulate the growth and performance of the copper foil. The most common is to add promoters SPS or polyethylene glycol (PEG) to promote and control the deposition of copper ions. However, the main function of SPS is to change the inhibitory effect in copper electrodeposition, promote the adsorption of copper ions on the electrode surface, and increase the deposition rate. Therefore, the use of SPS alone can only slightly reduce the size of the light-transmitting holes or pinholes formed in the copper foil.
[0038] Even if used with gelatin alone, it can only improve the roughness of the cathode surface to a certain extent and reduce the uneven distribution of current density. Therefore, the use of gelatin and SPS alone can only improve the flatness and roughness of the copper foil surface, thereby improving the physical properties of the copper foil to a certain extent, but it cannot remove the light-transmitting holes and pinholes in the copper foil.
[0039] The invention adds an acid copper strong dislocation agent to the commonly used additives SPS and gelatin. A certain content of the acid copper strong dislocation agent can be matched with SPS and gelatin to reduce light-transmitting holes and pinholes in the copper foil production process, thereby improving the quality of the copper foil and improving the physical properties of the copper foil.
[0040] The specific mechanism of action is as follows: AESS is a displacement agent used in the electroplating process, which can make the coating have better brightness and leveling and faster deposition speed. After being added to the additive, it can synergize with SPS and gelatin, on the one hand, promoting the activity of SPS, increasing the deposition rate of copper ions, and making SPS form an adsorption state, forming a stable thio complex in the electrolyte, increasing the copper ions on the surface of copper foil deposition, and inhibiting electrodeposition.
[0041] In addition, the most important thing is that after AESS is added to the electrolytic copper foil process, it can change the nucleation mechanism of copper deposition, greatly increasing the continuous nucleation rate of copper, close to the instantaneous nucleation rate; and AESS has a certain adsorption effect on the formed crystal plane, which can hinder the growth of the crystal plane, so the crystal plane with a slower production speed can be retained, and the crystal plane with a faster production speed becomes a point, and its formation is slowed down to a certain extent. Due to the above reasons, after a certain period of electrodeposition, the combination of AESS and SPS can change the preferential growth of copper, so that both the fast-growing crystal plane and the slow-growing crystal plane are retained to form a full texture, and the light-transmitting holes and pinholes originally formed by the slow-growing crystal plane are removed, ensuring the flatness of the copper foil surface and improving the physical properties of the copper foil.
[0042] AESS and gelatin can also produce synergistic effects. Since gelatin has both amino and carboxyl groups in its structure, gelatin has dual chemical properties. In acidic solutions, amino groups can easily obtain hydrogen ions, making gelatin micelles positively charged. During copper electrodeposition, the cathode surface has a certain degree of roughness, so the current density distribution on the cathode surface is uneven, resulting in uneven grain size of copper foil and increased roughness. The cations formed by gelatin can be adsorbed on the active points on the cathode surface, increasing the resistance of the active points, hindering the precipitation of copper ions, and improving the uniformity of copper ion precipitation at various locations on the cathode surface.
[0043] The addition of AESS can increase the concentration of hydrogen ions in the acidic electrolyte, activate gelatin, promote the combination of gelatin and hydrogen ions, and increase the rate of the above reaction. However, if only one type of gelatin is added, the dispersion of gelatin in the electrolyte is insufficient, making the preferential growth property of copper foil grains more obvious; therefore, the present invention uses two types of gelatin to react synchronously, which can produce synergistic effects with AESS respectively, increase the degree of disorder of various materials in the solution, and thus improve the dispersion of gelatin in the electrolyte.
[0044] The simultaneous action of the two gelatins can refine the grains, weaken the tendency of preferential growth of the crystal face, and can also form a charged complex with copper ions. The copper ions provide excess energy from the complex, which reduces the growth rate of the grains, is conducive to the generation of new crystal nuclei, and reduces the possibility of light-transmitting holes and pinholes.
[0045] The acid copper strong moving agent in the present invention is fatty amine ethoxy sulfonate (AESS), and can also be sodium mercaptoimidazole propane sulfonate (MESS) or polyethylene imine alkyl compound (GISS). The ratio of bone glue to collagen is 7:3, and the molecular weight is 18000-25000Da.
[0046] The invention also provides a method for using the additive for reducing the number of pinholes in copper foil.
[0047] The production of electrolytic copper foil includes the steps of copper dissolution, raw foil preparation and surface treatment. The additive solution in the present invention is added to the copper sulfate solution together with the electrolyte after the copper dissolution step. The method of use includes the following steps:
[0048] S1: Additive concentration configuration, add 5-8L of pure water to every 1g of additive to form an additive solution, and the addition flow rate of the additive solution is 5-20L / h;
[0049] S2: Production debugging, the additive is added before the solution inlet flowmeter, the initial addition flow of the additive solution is controlled at 5L / h, after the additive is configured, several raw foils are started for online polishing, the polishing parameters are speed 250 / swing 230, during the polishing process, it is necessary to pay attention to whether there is a color difference change on the copper foil surface, if there is an obvious color difference change, stop the machine immediately for adjustment;
[0050] S3: Visual inspection: after polishing is completed, the speed is increased to 6 microns, and a copper foil sample with a size of 50cm*1380mm is cut and visually inspected on a light box to determine the number of light-transmitting points or pinholes on the copper foil sample and compare it with the preset number. If the number of light-transmitting points or pinholes is greater than the preset number, the flow rate of the additive solution is increased, and the production debugging and visual inspection steps are repeated;
[0051] S4: Stable production. After production debugging and visual inspection, determine the qualified additive solution addition flow rate, enter the stable copper foil production process, and conduct concentration inspection and flow calibration of the additive solution every 2 hours.
[0052] In step S1 of configuring the concentration of additives, 6 to 6.5 L of pure water is preferably added to every 1 g of additive to prepare the additive solution; in step S2 of production debugging, the addition flow rate of the additive solution is increased by 5 L / h each time.
[0053] Not only the content of the additive will affect the quality of copper foil, but also the way and amount of additives used will have a great impact on the number of pinholes on the surface of copper foil. The concentration of additives in the electrolyte is the biggest factor affecting the quality of copper foil.
[0054] If the concentration of additives in the electrolyte is too high, it will easily lead to the formation of more complexes in the electrolyte, requiring more energy and time to reduce the copper ions. Under the same production time, the number of copper ions reduced is small, which affects the quality of the copper foil and greatly increases the time and cost required for copper foil production.
[0055] If the concentration of the additive in the electrolyte is too low, it will easily lead to uneven concentration of the additive in the electrolyte and poor dispersion of the overall solution, resulting in different concentrations and speeds of copper ion reduction at different locations, making the surface thickness of the copper foil uneven and affecting the quality of the copper foil.
[0056] The concentration of additives in the electrolyte is affected by two factors: one is the concentration ratio of the additives themselves, and the other is the flow rate of the additive solution added to the electrolyte. The flow rate of the additive solution also needs to be adjusted within a certain range according to the different concentrations of the electrolyte and copper sulfate.
[0057] By adding the additives in the use method of the present invention, the dispersion of each component in the solution can be ensured to be good, and the light-transmitting holes or pinholes formed after the copper foil is produced can be reduced. In addition, the warping, hard wrinkling and edge tearing of the copper foil can also be reduced.
[0058] In the present invention, the quality of copper foil produced at different concentrations of additives in the electrolyte was tested. The experiment is divided into several embodiments, and the experimental steps in each embodiment are the same, and the difference lies in the concentration and addition flow rate of the additive. Finally, the finished copper foil sample with a size of 50cm*100cm was cut, and the number of light-transmitting holes or pinholes on the copper foil of each embodiment was recorded, as shown in Table 1.
[0059] Table 1 Dilution and addition flow rate of additives in different embodiments
[0060]
[0061] The number of pinholes on the copper foil obtained by testing is shown in Table 2.
[0062] Table 2 The number of pinholes / light-transmitting holes in the copper foil samples obtained in different embodiments
[0063]
[0064] As shown in Table 2, the optimal concentration range of the additive solution is 6 to 6.5 L of pure water per 1 g of additive. Within this range, the removal ability of pinholes or light-transmitting holes on the surface of the copper foil is the strongest. The present invention also determines that the optimal ratio of the additive concentration is 220 L of pure water per 35 g of additive. The additive solution has the best effect at this concentration.
[0065] It can also be determined that the optimal range of the additive solution addition flow rate is between 10 and 15 L / h.
[0066] The present invention also tests the effects of different concentrations of substances in the additive on the physical properties of the copper foil, and the test method is as follows:
[0067] 1. When testing the tensile strength and elongation of copper foil, cut 0.5 inch × 6 inch specimens from the copper foil on a RGT-0.5A microcomputer-controlled motor universal testing machine (chuck speed 50.8 mm / min, gauge length 50 mm) with reference to the American Electronic Circuit and Electronic Interconnect Industry Association TPC-TM650, and test the mechanical properties at room temperature.
[0068] 2. Surface roughness test: The surface roughness of the copper foils prepared under different electrodeposition process conditions was tested by using a German Perthometer M1 roughness meter. Each sample was measured 10 times and the average value was taken.
[0069] In the present invention, the experiment is divided into several embodiments, and the experimental steps in each embodiment are the same, and the difference lies in the concentration of different substances, and the specific situation is shown in Table 3.
[0070] Table 3 Concentration of substances in different embodiments
[0071]
[0072] After the copper foil tensile strength and elongation tests, as well as the surface roughness tests, the test data results are shown in Table 4.
[0073] Table 4 Physical properties of copper foil samples in different embodiments
[0074]
[0075] It can be seen from Table 4 that among the additives, the optimal content of fatty amine ethoxy sulfonate is 0.16 g / L, the optimal content of SPS is 0.04 g / L, and the optimal content of gelatin is 0.02 kg / L. Under this condition, the copper foil produced has the best physical properties and excellent surface roughness.
[0076] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.
Claims
1. A method for using an additive for reducing the number of pinholes in copper foil, wherein the production of copper foil includes copper dissolving, raw foil preparation and surface treatment steps, characterized in that: The additive is added to the copper sulfate solution together with the electrolyte after the copper dissolving step, and the method of use comprises the following steps: S1: additive concentration configuration, the additive comprises water and the following concentration substances: acid copper strong moving agent 0.08-0.2g / L sodium polydisulfide propane sulfonate (SPS) 0.02-0.05g / L gelatin 0.01-0.04kg / L; gelatin is bone glue and collagen, the ratio of bone glue to collagen is 7:3, and the molecular weight is 18000-25000Da; 5-8L of pure water is added to every 1g of additive to form an additive solution, and the addition flow rate of the additive solution is 5-20L / h; S2: production debugging, the additive is added to the solution Before the liquid flow meter is fed, the initial addition flow rate of the additive solution is controlled at 5L / h. After the additive is configured, several raw foil machines are started for online polishing. The polishing parameters are speed 250 / swing 230. During the polishing process, attention should be paid to whether there is a color difference change on the copper foil surface. If there is an obvious color difference change, the machine should be stopped and adjusted immediately; S3: Visual inspection. After the polishing is completed, the speed is increased to 6 microns, and a copper foil sample with a size of 50cm*1380mm is cut. Visual inspection is performed on the light box to measure the number of light-transmitting points or pinholes on the copper foil sample and compare it with the preset number. If the number of light-transmitting points or pinholes is greater than the preset number, the addition flow rate of the additive solution is increased, and the production debugging and visual inspection steps are repeated; S4: Stable production, after production debugging and visual inspection, determine the addition flow rate of qualified additive solution and enter the stable copper foil production process; In step S4, the concentration of the additive solution needs to be inspected and the flow rate calibrated every 2 hours.
2. The method for using an additive for reducing the number of pinholes in copper foil according to claim 1, characterized in that: In the step S1, 6 to 6.5 L of pure water is added to every 1 g of additive to prepare the additive solution, and the optimal amount is to add 220 L of pure water to every 35 g of additive.
3. The method for using an additive for reducing the number of pinholes in copper foil according to claim 1, characterized in that: In the production debugging step, the flow rate of the additive solution is increased by 5 L / h each time, and the optimal range of the flow rate of the additive solution is 10 to 15 L / h.
Citation Information
Patent Citations
Ultrathin two-faced bright electrolytic copper foil in high performance, and preparation method
CN1958863A
Additive for electrolytic copper foil, ultra-low peak HVLP copper foil and preparation method of ultra-low peak HVLP copper foil
CN110724979A
Additive for improving 4.5-micron lithium ion electrolytic copper foil pinholes
CN112760682A
Method for adding additive for preventing edge tearing of 4.5-micron copper foil
CN113416985A